PENERAPAN METODE PEMBELAJARAN AKTIF COURSE REVIEW HORAY TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 11 PADANG - Novitri, Linda - (STKIP PGRI Sumbar, 2014)
This research was conducted due to the studentsâ low mathematics conceptual understanding and the discussion which was dominated by the students having higher ability. This then had made the learning process became unpleasant. This was an experimental research which used random toward the subject design. The population of the research was all of the first year students of SMPN 11 Padang registered in Academic Year 2013/2014. As the sample, the students in class VII.E was taken as the experimental group, and those in class VII.D was chosen as the control group. The instrument of the research was an essay post-test whose reliability was r11=0,74. The data gotten was analyzed by using MINITAB. The result of data analysis showed that P-value was 0,037 which was smaller than . Hence, it was concluded that mathematics conceptual understanding of the students taught by using Course Review Horay active learning method was better than that of students taught by using conventional laerning in the first year of SMPN 11Padang.